2020
DOI: 10.1002/jia2.25593
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for loss to follow‐up among at‐risk HIV negative men who have sex with men participating in a research cohort with access to pre‐exposure prophylaxis in coastal Kenya

Abstract: Introduction: Retention in preventive care among at-risk men who have sex with men (MSM) is critical for successful prevention of HIV acquisition in Africa. We assessed loss to follow-up (LTFU) rates and factors associated with LTFU in an HIV vaccine feasibility cohort study following MSM with access to pre-exposure prophylaxis (PrEP) in coastal Kenya. Methods: Between June 2017 and June 2019, MSM cohort participants attending a research clinic 20 km north of Mombasa were offered daily PrEP and followed monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
2
15
2
2
Order By: Relevance
“…We found that being LTFU was most frequent among individuals who were on PrEP, although we did not find significant differences in LTFU rates according to PrEP state. Determinants of becoming LTFU while on PrEP were: alcohol use disorder, residing further from the research clinic and having a secondary level of education or higher, consistent with recent findings in this study [24]. In addition, we found that being LTFU while on PrEP was more likely among men who resided in the area for 1 year or less.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that being LTFU was most frequent among individuals who were on PrEP, although we did not find significant differences in LTFU rates according to PrEP state. Determinants of becoming LTFU while on PrEP were: alcohol use disorder, residing further from the research clinic and having a secondary level of education or higher, consistent with recent findings in this study [24]. In addition, we found that being LTFU while on PrEP was more likely among men who resided in the area for 1 year or less.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we did not identify predictors for being LTFU while off PrEP, possibly owing to the lack of statistical power in identifying determinants from the small number of participants. However, our results suggest that linking MSM who have recently moved into an area to local MSM‐friendly services for social support and PrEP care services, screening for mental health and strengthened engagement may improve both retention in HIV‐1 prevention services and adherence to PrEP [24–26].…”
Section: Discussionmentioning
confidence: 99%
“…Frequency, type and quantity of alcohol use may be more influential for adherence and retention in PrEP care. Despite restrictions imposed by the COVID‐19 pandemic and potential resulting changes in risk behaviour, short‐term retention in PrEP care was in line with other published data [30]. Since predictors of retention were not identified in our small study, larger studies to explore barriers to retention among young men and women who drink are NEEDED.…”
Section: Resultssupporting
confidence: 85%
“…In addition, alternative PrEP dispensing venues in Kenya including the use of community pharmacies can potentially expand the reach of PrEP to individuals and communities with discomfort seeking services at government-run facilities. PrEP-taking individuals may also benefit from a peer support model which has recently been shown to improve ART adherence among MSM in a pilot study in coastal Kenya [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%